Pengukuran Kebugaran Keseimbangan Online Menggunakan Modifikasi Standing Stork Test - Hidayatullah, Fajar; Zulkifli, Muhammad; Handayani, Heni Yuli; Shufi, Darus; Putri, Melly Nur Aulia (Jurnal Sporta Saintika, 2024)
The COVID-19 virus is one of several viruses that have hit the world so widely and evenly that it has had an impact on the world of education. Under these circumstances, education must continue to be carried out remotely. Education using ICT media and internet networks is one way to overcome distance education. The use of online learning media can make students more independent and experience different experiences when learning through video, audio and text. For physical education it will give more challenge when physical assesment have to carried out for measuring student physical achievement. Balance as physical fitness was the subject of this study that will be measure with a modificated standing stork test. The standing stork test can allegedly be carried out boldly. The homogeneity test obtains a significance value of 0.886 which has a value greater than 0.05, so it can be interpreted that the data distribution is homogeneous or comes from populations that have the same variance. To test the validity using the product moment correlation test, a significance value of 0.001 is obtained which has a value less than 0.05 so that online and offline data can be said to be valid. Because the data is not normally distributed, the parametric test cannot be carried out so that the non-parametric test is bound using the Wilcoxon test for its reliability test. A significance value of 0.112 was obtained for the right leg and 0.223 for the left leg which was greater than 0.05 so that it meant that there was no significant difference between online and offline implementation.